El anillado de aves en la Argentina. 1961-1964: Cuarto informe. Convenio entre el Instituto Nacional de Tecnología Agropecuaria y la Fundación Miguel Lillo: investigación sobre migraciones de aves - Olrog, C. C. (El Hornero, 1965)
Number of birds banded: The number of birds banded in Argentina has increased from the 3,937 specimens reported previously to a total of 5,923, representing 169 species. Banding in spring 1963: During the spring of 1963, banding activities were carried out in the province of Santa Fe, focusing on herons, and in Buenos Aires Province, targeting gulls, chimangos, caracaras, herons, ducks, and northern hemisphere migrants. However, these efforts yielded limited results due to adverse weather conditions. Recoveries: Phalacrocorax brasilianus, Brazilian Cormorant. Notably, 384 chicks were banded in May and June 1963 in the flooded areas of Figueroa, Santiago del Estero. Within less than six months, ten recoveries were recorded, indicating that the young birds follow a southern and southeastern route along the Salado River shortly after leaving the nest, often appearing in large flocks, as reported by local hunters. The farthest recovery occurred in southeastern Brazil, 1,400 kilometers from the breeding site. Additional recoveries in Tucumán and Jujuy during November and December likely correspond to birds returning from the Argentine Litoral or more distant southeastern areas, given that rivers in northwestern Argentina have little water in winter and spring, and Figueroa’s wetlands are dry from July to January. Netta peposaca, Rosy-billed Pochard. A second recovery is reported in southeastern Brazil confirms that the initial finding was not accidental; according to hunters, large numbers of this species arrive in late winter (August–September) at the lake systems south of Porto Alegre, Brazil.